Recent developments in solar energy-based absorption cooling systems. (2015) - Valarmathi, T.N.; Sekar, S.; Sekar, S.D.; Aditya, A.; Cawin, R.; Kumar, J. Kishore
Solar energy being renewable is the best source for several applications. Absorption systems are heat operated, which can use any low grade energy such as solar energy or waste heat and suitable for many applications such as heating, cooling, desalination, drying, etc. Combination of solar and absorption systems is an attractive option in view of reduced dependency on decreasing fossil fuels and to reduce environment impact. In this study, a review of the most recent developments in the area of solar energy-based absorption cooling systems has been done. Ammonia-water, water-lithium bromide, combined systems and economic studies have been reviewed.